Climate change and intergenerational equity : revisiting the uniform taxation principle on carbon energy inputs - Belfiori, María Elisa (2018)
Fil: Belfiori, María Elisa. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina